Partial Guidance of Electromagnetic Waves by a Parabolic Cylindrical Boundary Separating Two Chiral Media - Singh K.S.; Khastgir P.; Choudhury R.K. (My University, 2025)
An investigation has been made of the electromagnetic wave propagation in a medium with two regions, having different chiral admittances, separated by a parabolic cylindrical surface. The resulting guide is analogous to a circular chirowaveguide when the circle is degenerated into a parabola. The eigenvalue equation and the cutoff conditions of such a chirowaveguide have been derived for different special cases. © 1993, THE PHYSICAL SOCIETY OF JAPAN. All rights reserved.